👤
Efrosn95
a fost răspuns

a) (2X+11):3 - 4 = 3; b) 3×((X+2)-5=13
c)3×(2X-1)-32=73 d) 3×(2X-1)+32=77
f)2×(X+5)-X+3×(X-1)=35



Răspuns :

Răspuns:

a) (2x+11):3 -4 = 3

2x/3 + 11/3 -4 = 3

2x/3 +11/3 - 12/3 = 9/3 | · 3

2x + 11 - 12 = 9

2x + 11 = 21

2x = 10

x = 5

b) 3·(x+2)-5 = 13

3x + 6 - 5 = 13

3x + 1 = 13

x = 4

c) 3×(2X-1)-32=73

6x - 3 - 32 = 73

6x - 35 = 73

6x = 73 + 35

6x = 108

x = 18

d) 3×(2X-1)+32=77

6x -3 + 32 = 77

6x + 29 = 77

6x = 48

x = 8

f)2×(X+5)-X+3×(X-1)=35

2x +10 -x + 3x -3 = 35

x + 10 + 3x - 3 = 35

4x + 7 = 35

4x = 28

x = 7

Sper ca te-am ajutat!

Explicație pas cu pas:

Răspuns:

[tex]\bf a) ~(2x+11):3 -4 = 3~~\bigg|\cdot 3[/tex]

[tex]\bf (2x+11) -12 = 9[/tex]

[tex]\bf (2x+11) = 9+12[/tex]

[tex]\bf 2x+11 = 21[/tex]

[tex]\bf 2x = 21 -11[/tex]

[tex]\bf 2x = 10~~\bigg|:2[/tex]

[tex]\green{\boxed{\bf ~x = 5~}}[/tex]

______________________

[tex]\bf b)~~ 3\cdot(x+2)-5 = 13[/tex]

[tex]\bf 3\cdot(x+2) = 13+5[/tex]

[tex]\bf 3\cdot(x+2) = 18~~\bigg|:3[/tex]

[tex]\bf x+2 = 6[/tex]

[tex]\bf x = 6-2[/tex]

[tex]\blue{\boxed{\bf x=4}}[/tex]

______________________

[tex]\bf c)~~ 3\cdot (2x-1)-32=73[/tex]

[tex]\bf 3\cdot (2x-1)=73+32[/tex]

[tex]\bf 3\cdot (2x-1)=105~~~\bigg|:3[/tex]

[tex]\bf 2x-1=35[/tex]

[tex]\bf 2x=35+1[/tex]

[tex]\bf 2x=36~~~\bigg|:2[/tex]

[tex]\purple{\boxed{\bf~ x=18~}}[/tex]

______________________

[tex]\bf d)~~ 3\cdot (2x-1)+32=77[/tex]

[tex]\bf 3\cdot (2x-1)=77-32[/tex]

[tex]\bf 3\cdot (2x-1)=45~~~\bigg|:3[/tex]

[tex]\bf 2x-1=15[/tex]

[tex]\bf 2x=15+1[/tex]

[tex]\bf 2x=16~~~\bigg|:2[/tex]

[tex]\pink{\boxed{\bf~ x=8~}}[/tex]

______________________

[tex]\bf f)~~2\cdot (x+5)-x+3\cdot(x-1)=35[/tex]

[tex]\bf 2x+10-x+3x-3=35[/tex]

[tex]\bf 4x+7=35[/tex]

[tex]\bf 4x=35-7[/tex]

[tex]\bf 4x=28~~~\bigg|:4[/tex]

[tex]\red{\boxed{\bf~x=7~}}[/tex]